Multiphysical analysis of nanoparticles and their effects on plants. (28th October 2020) - Chowdhury, Mohammad Asaduzzaman; Shuvho, Md Bengir Ahmed; Hossain, Md Imran; Ali, Md Osman; Kchaou, Mohamed; Rahman, Atiqur; Yeasmin, Nilufa; Khan, Abdus Sabur; Rahman, Md Azizur; Mofijur, M.
Abstract: Nanoparticles are the magic bullets and at the leading edge in the field of nanotechnology, and their unique properties make these materials indispensable and superior in many areas, including the electronic field. Extensive applications of nanomaterials are incontrovertibly entering our living system. The increasing use of nanomaterials into the ecosystem is one of the crucial environmental factors that human being is facing. Nanomaterials raise noticeable toxicological concerns; particularly their accumulation in plants and the resultant toxicity may affect the food chain. Here, we analyzed the characterization of nanomaterials, such as graphene, Al2 O3, TiO2, and semi‐insulating or conducting nanoparticles. Quantitative evaluation of the nanomaterials was conducted and their commercialization aspects were discussed. Various characterization techniques, scanning electron microscopy, X‐ray diffraction, and ultraviolet rays were utilized to identify the morphology, phase, absorbance, and crystallinity. In addition, we analyzed the effects of nanomaterials on plants. The toxicity of nanoparticles has severe effects on loss of morphology of the plants. Potential mechanisms including physical and physiological effects were analyzed. In future studies, it is indispensable to assess widely accepted toxicity evaluation for safe production and use of nanomaterials. Abstract : Analysis of Nanoparticles and their effects on plants.